Rhein Derivative 4F Inhibits the Malignant Phenotype of Breast Cancer by Downregulating Rac1 Protein - Li, Xinxiao; Liu, Yunfeng; Zhao, Yuhua; Tian, Wei; Zhai, Lina; Pang, Huifeng; Kang, Jiankang; Hou, Huaxin; Chen, Yanhua; Li, Danrong (Frontiers in Pharmacology, 2020)
Background: Triple-negative breast cancer is one of the common malignant tumors with unfavourable prognosis in women worldwide, which urges the need for developing novel therapeutic drugs with more effective anti-tumor ability. Rac family small GTPase 1 (Rac1) play important roles in malignant biological behavior and have been confirmed as a promising therapeutic target. Here we reported Rhein derivative 4F, and investigate the inhibition of Rhein and derivative 4F targeting Rac1 protein of breast cancer cells in vitro. Methods: Molecular docking software was used to simulate the interaction mode of Rhein and derivative 4F with Rac1 protein. Cell proliferation inhibited by derivative 4F was investigated in two breast cancer cells (MDA-MB-231 and MCF-7) and normal breast cell (MCF-10A) by cell counting kit-8 assay and growth curves. The role of derivative 4F in cell migration and invasion, cytoskeleton and regulation of Rac1 promoter activity and protein expression level was determined by Transwell chambers assay, F-actin staining, luciferase reporter gene assay and western blot assay, respectively. Results: Compared with Rhein, the derivative 4F binds to Rac1 more stably, and showed stronger ability in inhibiting the proliferation, migration and invasion of breast cancer cells, it also can cause cytoskeletal changes, and down-regulates the expression of Rac1 at the transcription and translation level more effectively. Conclusions: Rhein derivative 4F is a new anthraquinone compound with better anti-tumor activity than the lead compound Rhein in breast cancer. It can inhibit Rac1 expression and may be a small molecule inhibitor of Rac1.